Initial experience of irreversible electroporation ablation in Brazil: a retrospective analysis - Setuguti, Daniel Takeshi; Oliveira, Daniel Simões; Martins, Grace Gadelha; Braghiroli, Oddone Freitas Melro; Macedo, Antonio Luiz Vaconcellos; Siqueira, Luiz Tenorio de Brito (Brazilian Journal of Oncology, 2022)
Introduction: The objective of our study is to present the first Brazilian irreversible electroporation experience in the treatment of solid cancer.Material and Methods: A retrospective study with the first ten patients who underwent percutaneous or surgical IRE to treat solid cancer between March 2021 and May 2021. Preoperative data collection included patient demographics along with previous oncologic treatments. Operative and post-operative assessment involved number of probes, number of pulses, initial and final current and 30-days complications.Results: Primary tumor was locally advanced pancreatic cancer (70%), colorectal hepatic metastasis (20%), and cholangiocarcinoma (10%). All patients had previously undergone chemotherapy with stable disease in 80% and partial response in 20% before IRE. Eighty percent of the procedures was performed surgically and 20% percutaneously CT-guided. The mean procedure time of IRE was 38 minutes. Adverse events occurred in 4 patients (40%), all being grade I-II complications.
Keywords: Radiology, Interventional; Ablation techniques; Pancreatic neoplasms; Liver neoplasms